WHY DECOLONISATION AND NOT TRANSFORMATIVE CONSTITUTIONALISM (The Pretoria Student Law Review, 2021)
Paul Mudau and Sibabalo Mtonga proffer ‘Extrapolating the role of transformative constitutionalism in the decolonisation and Africanisation of Legal Education in South Africa’ to contribute to the ongoing dialogue about South Africa’s LLB curriculum, and to make studied comments about the need to shift from colonial modes of knowing, thinking, and doing. Their article does well to study the strides that have been made in this discourse, as they make use of the University of Pretoria’s Curriculum Transformation Document as one example of the progress that has been made. Mudau and Mtonga conclude that adherence to transformative constitutionalism may enhance decolonisation and Africanisation, and thus lead to the gradual transformation of legal education in South Africa. This rejoinder sets the argument from a different starting point — it insists that the definitive thrust of the Decolonial Turn in South Africa presents a decided critique of the 1994 constitutional arrangement, therefore rendering transformative constitutionalism a misfit in the quest to decolonise and Africanise South African legal education. This article concludes by asserting that South African law teachers, and anyone interested in the quest to alter colonial pedagogies, should concern themselves with seeking definitional clarity, and the rest shall follow.
Keywords: constitutionalism; constitution; transformation; decolonisation; decoloniality; epistemicide; legal education